miR-27a-3p Targets ATF3 to Reduce Calcium Deposition in Vascular Smooth Muscle Cells - Nakwon Choe; Duk-Hwa Kwon; Juhee Ryu; Sera Shin; Hye Jung Cho; Hosouk Joung; Gwang Hyeon Eom; Youngkeun Ahn; Woo Jin Park; Kwang-Il Nam; Young-Kook Kim; Hyun Kook (Elsevier, 2020)
Vascular calcification, the ectopic deposition of calcium in blood vessels, develops in association with various metabolic diseases and atherosclerosis and is an independent predictor of morbidity and mortality associated with these diseases. Herein, we report that reduction of microRNA-27a-3p (miR-27a-3p) causes an increase in activating transcription factor 3 (ATF3), a novel osteogenic transcription factor, in vascular smooth muscle cells. Both microRNA (miRNA) and mRNA microarrays were performed with rat vascular smooth muscle cells, and reciprocally regulated pairs of miRNA and mRNA were selected after bioinformatics analysis. Inorganic phosphate significantly reduced the expression of miR-27a-3p in A10 cells. The transcript level was also reduced in vitamin D3-administered mouse aortas. miR-27a-3p mimic reduced calcium deposition, whereas miR-27a-3p inhibitor increased it. The Atf3 mRNA level was upregulated in a cellular vascular calcification model, and miR-27a-3p reduced the Atf3 mRNA and protein levels. Transfection with Atf3 could recover the miR-27a-3p-induced reduction of calcium deposition. Our results suggest that reduction of miR-27a-3p may contribute to the development of vascular calcification by de-repression of ATF3.